Variant selection during mechanically induced martensitic transformation of metastable austenite by nanoindentation. (15th July 2015) - Kim, Yanghoo; Ahn, Tae-Hong; Suh, Dong-Woo; Han, Heung Nam
Abstract : Multiple pop-in events which indicate a gradual transformation from a metastable austenite grain to martensites in steel were detected during nanoindentation. It was observed by means of an automotive mapping technique with TEM that the partial volume of prior austenite had transformed into several martensite blocks with different variants. From a finite element calculation combined with phenomenological approach for martensitic transformation, it was confirmed that each variant corresponded to those for which the transformation strain effectively accommodates external stress.